he Social Crisis of Peru in the Facebook Posts of Five Press Media: News Coverage, Themes and Participating Actors Representation - Robles Olivos, Rafael (2023)
This article presents an investigation about the posts made on Facebook by five important press media in Peru (El Comercio, Exitosa Noticias, Expreso, Peru21 and RPP Noticias) during the social crisis of that country which was produced after the failed coup d’état of former President Pedro Castillo. As part of the methodological strategy, a temporal frame of study was establi-shed, ranging from December 10, 2022, date when the protests began, until forty days later, on January 18, 2023. In a next stage, through a descriptive analysis that combines quantitative and qualitative techniques, as well as the application of the Ideological Square Theory to recognize the emphasis that journalistic contents give to the participating actors, it was shown that the majority of the media examined pays more attention to protests, to acts of violence, and to the agents of power (Government and security forces) over the deceased, who are counted by the dozens. In the same way, a noticeable tendency to link the protests with violence and fatal victims was revealed, and a possible responsibility for these incidents on the part of the current regime is omitted.